If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7j + 4 = 5j Reorder the terms: 4 + 7j = 5j Solving 4 + 7j = 5j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-5j' to each side of the equation. 4 + 7j + -5j = 5j + -5j Combine like terms: 7j + -5j = 2j 4 + 2j = 5j + -5j Combine like terms: 5j + -5j = 0 4 + 2j = 0 Add '-4' to each side of the equation. 4 + -4 + 2j = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2j = 0 + -4 2j = 0 + -4 Combine like terms: 0 + -4 = -4 2j = -4 Divide each side by '2'. j = -2 Simplifying j = -2
| -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 | | -(x+5)=-1 | | 5h-12=4h+6 | | 3(-4+3)=2 | | 8x^4-42x^2=0 | | 2(1[3u-7]1)=16 | | 2,5x-21=14 | | -4.6y=9.2 | | (8x^4-42x^2-10x)-3=0 | | 1-7(-2-8a)=-433 | | (-2)+(-3)+(-2)= | | 0,5x-3=15 | | -2x+1=-18 | | 3x-4(x-8)=34 |